(untitled) (Вісник: Міжнародні відносини, 2024)
The article analyzes the optimal directions and ways of development of international cooperation, capacity building and reform of Ukrainian special services in the view of the current geopolitical situation, as well as current and future challenges to Ukrainian and European security.